Speed Controlled Composite Fabrication Using DC Motor - Agus Jatmiko; Ismudiati Puri Handayani; Asep Suhendi (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
Fabrication process determines the composite quality. Conventional method such as dry- and hand lay-up are commonly used. Dry lay-up method has known to be more controllable and produce less defect composites with good mechanical property. However, this method is more expensive. On the other hand, hand lay-up which is more simple and less expensive, is uncontrollable as well as produces more defect and poorer mechanical properties of composites. In this study, we creates instrument which is able to control wet lay-up fabrication process of Fiber Reinforced Composite Material (FRCM). Instead of using uncontrollable human hands, this instrument utilizes speed controllable paint roller which distributes the resin though all matrix. The result shows that the produced composites have more homogenous resin distribution, smaller size defects, and exhibits stronger mechanical properties compare to the one produced by hand lay-up method. This study is expected to open further innovations on low cost composite fabrication.